The Application of Simons’ “Levers of Control” in the Quran and Sunna - Mohd Balwi, Mohd Abd Wahab Fatoni; Che Abdullah, Ahmad Sufian; Lubis, Asmuliadi (Brill Academic Publishers, 2018)
Simons'1 “levers of control” is a strategy-based framework that takes into consideration the belief systems of and the functions and interactions within an organization. The purpose of this article is to discuss Simons' levers of control from an Islamic viewpoint, based on the teachings of the Quran and Sunna. It demonstrates that the concept of “levers of control”, as posited by Simons, does not contradict the basic tenets of Islam. In fact, all the main components of the levers of control - belief system, boundary system, diagnostic control system, and interactive system - were actually emphasized and vigorously implemented by Prophet Muhammad SAW. However, these practices have never before been organized into well-arranged and systematic categories that can be used as guidelines by Islamic organizations. Such organizations should aspire to implement comprehensively the practices of Prophet Muhammad SAW in all aspects of organizational management functions, including those related to control. However, in the absence of clear and comprehensive guidelines, any implementation may not be appropriate or in accordance with the practices of Prophet Muhammad SAW. More importantly, incorrect implementation as a result of limited understanding or misunderstanding of the Prophet's SAW practices can affect the overall perception of Islam. By properly utilizing the levers of control, organizations that strive to emulate the practices of Prophet Muhammad SAW in their operations can be successful.